2008
DOI: 10.1007/s00431-008-0787-x
|View full text |Cite
|
Sign up to set email alerts
|

Parental perception of weight and weight-related behaviour in 2- to 4-year-old children in the eastern part of the Netherlands

Abstract: Parental perception of weight status and weightrelated behaviour of their toddler was determined through a questionnaire survey in child health care centres (CHCs). Complete data on weight, length, sex and age were available for 635 of 682 children (93.1%). The median age of the children was 37.0 months (range 24-56 months). Of all 635 children, 76.5% were normal weight, 16.2% underweight and 7.2% overweight. Parents' perception of the weight of their child compared with their peers was moderately related to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 17 publications
2
7
0
1
Order By: Relevance
“…Our percentages of parents' underestimation of their overweight children's weight status are consistent with previous studies, which range from 50% to 85% [17,20,22,24,26]. Our finding that parental underestimation among overweight and obese children is higher in younger children is also consistent with previous studies [16-18, 20, 41-44].…”
Section: Comparison With Other Literaturesupporting
confidence: 92%
See 1 more Smart Citation
“…Our percentages of parents' underestimation of their overweight children's weight status are consistent with previous studies, which range from 50% to 85% [17,20,22,24,26]. Our finding that parental underestimation among overweight and obese children is higher in younger children is also consistent with previous studies [16-18, 20, 41-44].…”
Section: Comparison With Other Literaturesupporting
confidence: 92%
“…Moreover, insight into the change of the parents' perception of their child's weight status over time is missing. With the exception of age, no Dutch studies have found any clear moderating factors [22,[24][25][26]. Importantly, no Dutch study to date has examined parents' perception of their child's weight status with an age range of children 2 to 12 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…A Dutch study showed that only 34% of the parents of young children had sufficient knowledge on causes of overweight, 61% on the consequences of overweight, and 49% on healthy food [36]. Other studies in the Netherlands found that 50% of the parents did not recognize overweight in their child and 87% of the parents with an overweight child did not worry about their child's weight [37], [38]. To tackle the overweight problem, intervention programs that lead to long-lasting lifestyle changes and reductions in the prevalence of overweight and obesity are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Parents’ weight misperception seems to affect how worried they are about the weight status of their children [24]. More specifically, parents who underestimate the weight status of overweight children are less concerned with their weight than those who recognize their children as overweight [25].…”
Section: Introductionmentioning
confidence: 99%